Evaluating a digital mental health intervention for people with Parkinson's (PACT): acceptability and feasibility randomised controlled trial. - Pinto, Cathryn; Norton, Sam; Cubi-Molla, Patricia; Hurt, Catherine; Chowdhury, Sulayman; Dooley, Niamh; Safwi, Aamina; Brown, Jennie; Volpato, Riccardo; Stumpf, Simone; McCracken, Lance; Bogosian, Angeliki (Aging & Mental Health, 2025)
Objectives: We developed a web application (PACT app) based on Acceptance and Commitment Therapy to support mental health for people with Parkinson's. Here, we assess the app's acceptability and the feasibility of conducting a randomised controlled trial to evaluate its effectiveness. Method: This was a two-armed parallel group design with 2:1 allocation to the PACT app or waiting-list control and a single, post-intervention follow-up. Feasibility outcomes included recruitment and retention rate, intervention engagement and satisfaction. Secondary outcomes included measures of anxiety, depression, quality of life, and cost-effectiveness. Treatment effects for secondary outcomes were estimated using linear regression, following the intention-to-treat principle. Results: Fifty-seven people with Parkinson's were randomised to 4 weeks of PACT app (n = 38) or waiting-list control (n = 19). Recruitment, retention rate, intervention use, and acceptability met our progression criteria. Intervention effects were in the expected direction for all outcomes and largest for measures of depression (Hedges g = −0.96; 95% CI = −1.47 to −0.46) and committed action (Hedges g = 0.87; 95% CI = 0.38 to 1.35). Conclusion: Progression criteria were met, and PACT was acceptable to people with Parkinson's. It has potential efficacy and cost-effectiveness. A future larger trial to fully evaluate efficacy is needed. Trial registration: ISRCTN65177345 (01/09/2023).